Peptidoglycan Recognition Protein 4 Limits Bacterial Clearance and Inflammation in Lungs by Control of the Gut Microbiota - Dabrowski, Alexander N.; Shrivastav, Anshu; Conrad, Claudia; Komma, Kassandra; Weigel, Markus; Dietert, Kristina; Gruber, Achim D.; Bertrams, Wilhelm; Wilhelm, Jochen; Schmeck, Bernd; Reppe, Katrin; N'Guessan, Philippe D.; et al. (Frontiers in Immunology, 2019)
Streptococcus pneumoniae is the most frequent cause of community-acquired pneumonia. Endogenous host defense molecules such as peptidoglycan recognition protein 4 (PGLYRP4) might influence the course of this disease. To the best of our knowledge, there are no reports on the relevance of PGLYRP4 in pneumonia. Therefore, wild type (WT) and PGLYRP4-deficient (PGLYRP4KO) mice were analyzed in an in vivo and in vitro experimental setting to examine the influence of PGLYRP4 on the course of pneumococcal pneumonia. Furthermore, caecal 16S rRNA microbiome analysis was performed, and microbiota were transferred to germfree WT mice to assess the influence of microbiotal communities on the bacterial burden. Mice lacking PGLYRP4 displayed an enhanced bacterial clearance in the lungs, and fewer mice developed bacteremia. In addition, an increased recruitment of immune cells to the site of infection, and an enhanced bacterial killing by stronger activation of phagocytes could be shown. This may depend partly on the detected higher expression of complement factors, interferon-associated genes, and the higher proinflammatory cytokine response in isolated primary PGLYRP4KO vs. WT cells. This phenotype is underlined by changes in the complexity and composition of the caecal microbiota of PGLYRP4KO compared to WT mice. Strikingly, we provided evidence, by cohousing and stable transfer of the respective WT or PGLYRP4KO mice microbiota into germfree WT mice, that the changes of the microbiota are responsible for the improved clearance of S. pneumoniae lung infection. In conclusion, the deficiency of PGLYRP4, a known antibacterial protein, leads to changes in the gut microbiota. Thus, alterations in the microbiota can change the susceptibility to S. pneumoniae lung infection independently of the host genotype.